Runoff and erosion mitigation via conservation tillage and cover crops - derivation of model input parameters from literature - Stephan Sittig; Robin Sur (Environmental Challenges)
Runoff and hydric soil erosion from agricultural fields may lead to a transfer of plant protection products (PPP) to adjacent surface water bodies, in addition to the intrinsic losses of water and topsoil material for plant production. Measures of conservation agriculture are known to be suitable for mitigating these processes. In this study, the pertinent literature on runoff and erosion mitigation following the application of measures from the conservation agriculture toolbox was reviewed to determine the reduction effects of distinct strategies of conservation tillage and the use of cover crops. In total, 1483 and 1076 single data points were considered for runoff and erosion, respectively. We calculated geometric means (with confidence intervals expressed by the geometric SD factor) of the ratios of quantities derived from treated vs. untreated setups following no-tillage of 0.44 [0.17–1.13; n=38 studies] and 0.11 [0.03–0.93; n=37] for runoff and erosion, respectively. Conservation tillage measures other than no-tillage (i.e., reduced tillage, e.g., strip tillage) led to ratios of 0.46 [0.22–0.94; n=42] and 0.18 [0.06–1.16; n=35]. The use of cover crops resulted in ratios of 0.41 [0.19–0.88; n=33] and 0.09 [0.01–0.65; n=30]. Corresponding runoff curve numbers to be included in numerical simulations were calculated to be reduced by 11 % [5 %–25 %; n=16], 10 % [4 %–21 %; n=21], and 12 % [5 %–30 %; n=19], for the three categories of conservation agriculture (no-till, reduced-till, cover crops), respectively. That is equivalent to absolute reductions of the CN scores by 7 [4–13], 5 [2–13], and 5 [2–12]. Analogous PPP transport ratios of treated vs. non-treated are 0.50 [0.13–1.92; n=19], 0.70 [0.29–1.70; n=11], and 0.46 [0.12–1.80; n=4], respectively. This work broadens the database to include no-tillage, conservation tillage and cover crops into the framework of environmental exposure assessment for the registration of plant protection products.